2010
DOI: 10.1186/1471-2296-11-62
|View full text |Cite
|
Sign up to set email alerts
|

Patient understanding of moles and skin cancer, and factors influencing presentation in primary care: a qualitative study

Abstract: BackgroundMelanoma incidence in the UK has doubled over two decades, yet there is conflicting evidence about factors which prompt or delay patients seeking advice. Aim: To explore patient understanding of pigmented skin lesions (moles) and skin cancer, and factors which influence seeking help in primary care.MethodSemi-structured interviews with forty MoleMate Trial participants, analysed using the theoretical framework of the Safer-Andersen model of Total Patient Delay.ResultsPatient understanding and awarene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 25 publications
1
34
0
Order By: Relevance
“…Walter et al (2010) reported that cancer risk assessment of skin moles was heavily influenced by the nonmedical literature and experiences of family and friends, and was not congruent with medical opinion. The importance of informal knowledge about illness in individuals' health beliefs and decisions was also reported by Cytryn et al (2009) in relation to myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Walter et al (2010) reported that cancer risk assessment of skin moles was heavily influenced by the nonmedical literature and experiences of family and friends, and was not congruent with medical opinion. The importance of informal knowledge about illness in individuals' health beliefs and decisions was also reported by Cytryn et al (2009) in relation to myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients have perceived themselves to be “low-risk” [11] and have reported a lack of general malaise, which might have contributed to delay [12]. Patients have also noted that they worry about attending their general practitioner (GP) for fear of creating a “fuss” [13].…”
Section: Discussionmentioning
confidence: 99%
“…ICD-10 coding was used as an indicator for body site but this method of grouping included a combination of different histological subtypes within the same code. Patients with early melanoma tend to feel well and, as a result, may not heed the initial symptoms [12]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schmid-Wendtner and colleagues 31 similarly found that longer time to biopsy was not associated with greater tumor thickness, while fairer skin type, lower education level, and lack of knowledge about melanoma were associated with greater tumor thickness. Walter and colleagues 32 found that patient lack of concern regarding a changing nevus was a significant barrier to early detection. In this study, we have identified several additional factors associated with delayed melanoma diagnosis, including location on trunk and extremities, new patient status, patient concern before biopsy, and physician suspicion of NMSC.…”
Section: Discussionmentioning
confidence: 99%